Peningkatan Kemampuan Kolaborasi dan Pemecahan Masalah melalui Model Cooperative Learning Tipe Teams Games Tournament (TGT) pada Siswa Kelas IV SDN 5 Cakranegara - Mulyati, Eva; Sujana, I Made; Taufiqurrahman, Irwan (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2025)
This study aims to evaluate the effectiveness of the Teams Games Tournament (TGT) learning model in improving students’ problem-solving and collaboration skills. The research was motivated by classroom observations indicating low student engagement and suboptimal group cooperation, which in turn affected students’ problem-solving abilities. The study employed a Classroom Action Research (CAR) design conducted in two cycles, each consisting of planning, implementation, observation, and reflection phases. The results showed a significant improvement in students’ problem-solving skills, with the average score increasing from 70 in the first cycle to 86.5 in the second cycle (a 23.6% increase). Collaboration skills also improved substantially, from 65% to 85.67% (a 31.8% increase). In addition, teacher activity levels rose from 78.5% (good) to 91.8% (very good). These improvements were attributed to more effective strategies in guiding tournaments and delivering materials interactively. In conclusion, the implementation of the Teams Games Tournament (TGT) model successfully enhanced students’ problem-solving and collaboration skills while fostering more active teacher engagement in the learning process. This model provided students with opportunities to discuss, express opinions, and work together more effectively in completing learning tasks.